PENILAIAN KINERJA BALAI REHABILITASI SOSIAL EKS PENYALAHGUNA NAPZA MANDIRI SEMARANG - Roni Budi Utomo; Nina Widowati (Journal of Public Policy and Management Review, 2016)
This research will describe and analyze the performance of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang, and aspects that support and hinder. The theory used in this research are five dimensions of performance, which are productivity, quality of service, responsiveness, responsibility, and accountability. This research used interviews, observation, documentation, and literature to collected data. Technique used for selecting the informants is snowball technique. The result of this research indicate that the performance of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang is not optimal. Productivity of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang is good enough, but still constrained at the lack of professionals in human resources, and the development of infrastructure is constrained in the budget. Quality service of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang is not good enough because there is lack of support from human resources and facilities. Responsiveness of Social Rehabilitation Center for ex drug abusers Mandiri Semarang is good enough. Responsibility of Social Rehabilitation Center for ex drug abusers Mandiri Semarang is good. Accountability of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang is good because there is accountability and transparency. Aspects that support the performance of Social Rehabilitation Center for ex drugs abusers Mandriri (in) Semarang are the obvious of the division of labor for the employees, employee discipline, and cross-sectoral cooperation. Aspects that hinder the performance of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang are limited budget, lack of facilities and infrastructure support, and lack of human resources support in terms of quality and quantity. Based on the research, the performance of Social Rehabilitation Center for ex drug abusers Mandiri (in) Semarang there are some recommendations that can be given to optimize the performance, such as improving the quality and quantity of employees needed, submission of budget proposals for facilities and infrastructure, and community involvement in social rehabilitation program.